1997
DOI: 10.1103/physrevlett.78.1616
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Enhanced Multistability in Coupled Oscillator Systems

Abstract: We study nonequilibrium phenomena in a globally coupled oscillator system with a third harmonic pinning force in the presence of an additive noise and a fluctuating interaction. The system shows a subcritical saddle-node bifurcation from an asymmetric state to a symmetric state at a critical noise intensity leading to multistable states. The fluctuating interaction increases the critical noise intensity and thus enhances the multistability drastically. We show phase diagrams and discuss the nature of the phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(27 citation statements)
references
References 7 publications
2
25
0
Order By: Relevance
“…In the case of surface waves new states can be "stabilized" by noise and the bistable region of the deterministic system may be strongly enlarged by multiplicative noise. We note that "noise-enhanced multistability" has been reported in a simple model of coupled oscillators but also requires additive noise [35]. The structure of this model being of a very different nature than the one involved in parametric amplification, we expect that noise-induced bistability can be observed with other subcritical pattern-forming instabilities.…”
Section: Discussionmentioning
confidence: 95%
“…In the case of surface waves new states can be "stabilized" by noise and the bistable region of the deterministic system may be strongly enlarged by multiplicative noise. We note that "noise-enhanced multistability" has been reported in a simple model of coupled oscillators but also requires additive noise [35]. The structure of this model being of a very different nature than the one involved in parametric amplification, we expect that noise-induced bistability can be observed with other subcritical pattern-forming instabilities.…”
Section: Discussionmentioning
confidence: 95%
“…Arecchi and co-workers [7] have shown that the coexistence of basins of attraction in phase space may lead to the appearance of 1͞f noise. Systems that exhibit a large number of attractors lead to additional interesting phenomena, such as noiseinduced preference of attractor [8] and noise-enhanced multistability [9].In this Letter, the effect of noise is studied in a multistable system, which is a single-mode semiconductor laser with weak optical feedback. Feudel and Grebogi have shown that chaotic attractors are uncommon in multistable systems [10].…”
mentioning
confidence: 99%
“…Arecchi and co-workers [7] have shown that the coexistence of basins of attraction in phase space may lead to the appearance of 1͞f noise. Systems that exhibit a large number of attractors lead to additional interesting phenomena, such as noiseinduced preference of attractor [8] and noise-enhanced multistability [9].…”
mentioning
confidence: 99%
“…This multistable behavior occurs in many different fields like optics [1], chemistry [2], neuroscience [3], semiconductor physics [4], plasma physics [5] and coupled oscillators [6]. Moreover, addition of noise to multistable systems has led to several interesting phenomena, like noise-induced preference of attractors [7,8], directed diffusion [9], noiseenhanced multistability [10] and chaotic itinerancy [11]. The latter effect, which consists of hopping between different attractors caused by the noise, has also been observed experimentally in an optical system [12].…”
mentioning
confidence: 99%